Marketing and design in the service sector : enhancing the customer experience (Emerald Publishing Limited, 2024)
Marketing and Design in the Service Sector: Enhancing Customer Experience focuses on the new perspective of design in marketing within the service sector and how the space-scape and design-scape impacts on customer experience. The authors examine the most recent research to provide a new perspective on offline and online space in customer-oriented services, such as retail, healthcare, gyms, supermarkets, restaurants, cafes, hotels, leisure centres, airports, and banks. The importance of the environment and the product design have been discussed by many researchers in the past as part of design-scape. However, the COVID-19 pandemic brought unprecedented changes to the service industry. As a result, the product design, delivery design and setting of the sector faced a holistic change. The service sector constantly tries to provide customers with comfort, and, in the process, we witnessed many innovative ways to meet the demand, including, for instance, contactless delivery, or robots for delivery, in the healthcare industry. The travel and tourism industry also started attracting attention for significant innovations in terms of designing spaces through introducing space-scape and providing a unique stress-free experience for their customers (e.g. silent airport) to enhance experience-scape. The experiences gained from service digitalisation in a crisis also offer fruitful learning for digital innovation, transformation and service design and development. The authors provide a combination between theory and practice as well as relevant and fresh case studies that will prove invaluable to academicians and students with an interest in the Service Sector.
Keywords: Customer relations.; Marketing.; Customer services.; Business & Economics, Customer Relations.; elektronické knihy; electronic books